ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PEMASARAN RANGKA ATAP BAJA RINGAN DI DENPASAR - Astana, I Nyoman Yudha; Agung Yana, A. A. Gde; Dipta Setiawan, Nyoman Edi Dharma (JURNAL SPEKTRAN, 2019)
ANALYSIS OF FACTORS THAT INFLUENCE THE MARKETING OF LIGHT STEEL ROOF TRUSS IN DENPASAR ABSTRACT As the need for residence in Denpasar continues to increase, the demand for building materials, especially lightweight steel roof truss also increases. This leads to a tight competition among lightweight steel sellers. This study aimed at investigating factors that influence lightweight steel roof truss marketing in Denpasar and strategies that can be done by business people in facing such competition. This research used Factor Analysis and SWOT Analysis as a research approach. Questionnaires and interviews are used to assist the method of data colection. In Factor Analysis, selected respondents were the parties who understood the marketing strategy of lightweight steel roof truss in Denpasar. The SWOT Analysis was done on Company X, which sold lightweight steel roof truss in Denpasar. The respondents of the SWOT Analysis were two persons from internal company. Based on the results of Factor Analysis, three main factors was formed, namely product popularity, service quality and product attractiveness. Meanwhile, through SWOT Analysis, it was found that the company position is in quadrant I, so it supported the SO (Strength-Opportunity) strategy. This strategy maximized strength and utilized opportunities. It involved building new branches, increasing the quantity and variety of products, maintaining service and product quality, providing products that always follow the development of consumer tastes, efficiency of the company's operational costs, increasing the quantity of purchases of products to be traded and buying goods directly from the producers.